CONSTRUCTAL LAW AND MEDICINE CRISES IN ROMANIA (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
The document discusses the application of Constructal Law and Optimal Global Pricing technology to resolve the medicine crises in low and high-priced markets, focusing on the case of Romania.
Keywords: Global medicine crises; Low-priced markets; High-priced markets; Resistance to flow